2018
DOI: 10.1055/s-0037-1613685
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Operative Techniques and the Postoperative Complications for Bone-Anchored Hearing Aid Implantation

Abstract: Introduction  Bone anchored hearing aids (BAHA) represent a useful surgical option for patients with single sided deafness. Objectives  To compare multiple techniques for BAHA implantation regarding postoperative complications, operative time, and duration between the surgery and the first use of the BAHA. Methods  A retrospective study was conducted of all patients receiving implantation of a BAHA from August of 2008 to October of 2014. Data collected included: patient age, gender, side operated, abutment l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Recent publications report a single mild skin reaction in 20 to 30% of the implants and no revision surgery in a 3 to 5 year follow-up ( 7 , 30 ). Transcutaneous systems have been shown to be associated with less skin complications ( 31 ). In this study, skin complications were rare.…”
Section: Discussionmentioning
confidence: 99%
“…Recent publications report a single mild skin reaction in 20 to 30% of the implants and no revision surgery in a 3 to 5 year follow-up ( 7 , 30 ). Transcutaneous systems have been shown to be associated with less skin complications ( 31 ). In this study, skin complications were rare.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical outcomes of different techniques have varied over the years 9 . The most common complications addressed have been skin infections, flap necrosis and skin overgrowth as well as numbness and poor cosmetic appearance 10 . All of these complications can impact the satisfaction and acceptance of the device by patients.…”
Section: Discussionmentioning
confidence: 99%
“…Concern regarding pBAHDs normally surrounds complications, particularly related to skin infections. 6,7,17,22 A recent systematic review demonstrated an approximately fivefold reduced ratio of events to ears for adverse events when comparing pBAHDs to the Bonebridge. 23 Cosmetic issues related to percutaneous abutments are also a significant concern for many, with 30% in one large case series rejecting pBAHD surgery for such reasons.…”
Section: Clinical Applicability Of the Studymentioning
confidence: 99%
“…The presence of a percutaneous abutment with pBAHD commonly leads to skin complications with patients needing to perform daily abutment‐site skin care. Despite minimally invasive surgical approaches and advances in implant technologies, wound healing issues still affect nearly 25% of patients 5‐7 …”
Section: Introductionmentioning
confidence: 99%